Carers' experiences and coping strategies with down syndrome children - Zainal Abidin, Lydia (Universiti Malaysia Sarawak, UNIMAS, 2010)
This paper explores carers' experiences and their coping strategies employed in raising Down Syndrome children so as to provide insight into the wellness of carers and families with Down syndrome children.